Fossil Fuel Producing Economies Have Greater Potential for Industrial Interfuel Substitution - Steinbuks, Jevgenijs; Narayanan, Badri G. (Elsevier, 2014)
This study analyzes industrial interfuel substitution in an international context using a large unbalanced panel dataset of 63 countries. We find that compared to other countries fossil fuel producing economies have higher short-term interfuel substitution elasticities. This difference increases further in the long run as fossil fuel producing countries have a considerably longer adjustment of their fuel-using capital stock. These results imply lower economic cost for policies aimed at climate abatement and more efficient utilization of energy resources in energy-intensive economies.